2002
DOI: 10.4049/jimmunol.169.3.1482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rhinovirus Infection on Histamine and Cytokine Production by Cell Lines from Human Mast Cells and Basophils

Abstract: To understand the biochemical events that occur in the airways after rhinovirus (RV) infection, we developed for the first time a model in which the cell lines from human mast cells (HMC-1) and basophils (KU812) can be infected with RV14, a major group RV. Viral infection was confirmed by demonstrating that viral titers in culture supernatants, and RV RNA increased with time. RV14 infection alone and a combination of PMA plus calcium ionophore A23187, did not increase histamine production by these cells, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
49
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 34 publications
3
49
0
Order By: Relevance
“…Previous reports have shown that dengue virus infection of human MCs stimulates RANTES, macrophage inflammatory protein 1a, and macrophage inflammatory protein 1b, 24 which may recruit inflammatory cells to sites of infection. Still others have shown that rhinovirus infection alone does not alter cytokine production by human basophilic or MC lines 25 but can potentiate IgE-activated IL-4, IL-6, and IL-8 release. 25 These studies suggest that MCs recruit nearby inflammatory cells during a viral infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that dengue virus infection of human MCs stimulates RANTES, macrophage inflammatory protein 1a, and macrophage inflammatory protein 1b, 24 which may recruit inflammatory cells to sites of infection. Still others have shown that rhinovirus infection alone does not alter cytokine production by human basophilic or MC lines 25 but can potentiate IgE-activated IL-4, IL-6, and IL-8 release. 25 These studies suggest that MCs recruit nearby inflammatory cells during a viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Still others have shown that rhinovirus infection alone does not alter cytokine production by human basophilic or MC lines 25 but can potentiate IgE-activated IL-4, IL-6, and IL-8 release. 25 These studies suggest that MCs recruit nearby inflammatory cells during a viral infection. Our study suggests that MCs may also activate nearby cells to inhibit viral infection, because IFN-a activates various antiviral pathways 26 and greatly reduces virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study was limited to investigating a single RV14 infection titre (10 4 TCID 50 U/mL) of unknown MOI and focused on the modulation of PMA/ionomycin‐ or IgE/anti‐IgE‐dependent histamine and cytokine release 40. Our study has expanded the findings of Hosoda et al .…”
Section: Discussionmentioning
confidence: 96%
“…Influenza virus infection increases basophil LTC 4 release (Huftel et al 1992). Infection of respiratory viruses, including influenza virus and RV, also activates histamine release from peripheral blood basophils (Chonmaitree et al 1988;Huftel et al 1992) and human mast cells (Hosoda et al 2002). Furthermore, RV infection increases bronchial responsiveness to histamine (Gern et al 1997), and histamine content in bronchoalveolar lavage fluid in allergic subjects (Calhoun et al 1994).…”
mentioning
confidence: 99%
“…RV infection induces the production of several cytokines such as interleukin (IL)-1 and IL-6 in airway epithelial cells (Terajima et al 1997;Yamaya 2002) and human mast cells (Hosoda et al 2002), and increases IL-6 in nasal washing (Zhu et al 1996). Respiratory virus infections also induce the production of intercellular adhesion molecule-1 (ICAM-1) in the airway epithelial cells (Terajima et al 1997).…”
mentioning
confidence: 99%